Grid-connected photovoltaic systems for Malaysian residential sector: Effects of component costs, feed-in tariffs, and carbon taxes. (1st May 2016) - Lau, K.Y.; Muhamad, N.A.; Arief, Y.Z.; Tan, C.W.; Yatim, A.H.M.
Abstract: Blessed with abundant solar radiation, Malaysia has a huge potential for grid-connected PV (photovoltaic) installations, particularly for its fast-growing residential sector. Nevertheless, Malaysia's PV installation capacity is relatively small compared with the global PV capacity. Significantly, the pricing mechanisms for grid-connected PV projects need to be appropriately assessed to build up the public's confidence to invest in PV projects. In this paper, we analyze the effects of component costs, FiTs (feed-in tariffs), and carbon taxes on grid-connected PV systems in Malaysian residential sector using the HOMER (Hybrid Optimization of Multiple Energy Resources) software. Results demonstrate that the implementation of grid-connected PV systems is highly feasible with PV array costs of $ 1120/kW or lower. For higher PV array costs up to $ 2320/kW, introducing an FiT rate three times higher ($ 0.30/kWh) than the grid tariff for a 100 kW grid sale capacity will, NPC-wise, prioritize grid-connected PV systems over the utility grid. By implementing the FiT ($ 0.50/kWh) and the carbon tax ($ 36/metric ton) schemes simultaneously, grid-connected PV systems will remain as the optimal systems even for costly PV arrays (up to $ 4000/kW). The findings are of paramount importance as far as PV pricing variability is concerned. Highlights: Grid-connected PV for Malaysian residential sector has been analyzed using HOMER. Component costs, feed-in tariffs, and carbon taxes affect optimal system types. Grid-connected PV projects are feasible for low PV array costs ($ 1120/kW or lower). For higher PV array and inverter costs, feed-in tariffs should be implemented. Combining feed-in tariffs with carbon taxes are effective for further lowering NPCs.